2022
DOI: 10.1039/d2ya00204c
|View full text |Cite
|
Sign up to set email alerts
|

Can vehicle-to-grid facilitate the transition to low carbon energy systems?

Abstract: Vehicle-to-grid (V2G) is when electric vehicles (EVs) provide services to the power grid, such as shifting when they charge or discharging to serve peaks loads. At scale, an aggregator can...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The value of 𝑝 𝐸,𝑖𝑛𝑗 𝑡,𝑠 is a function of the relative share of injection going toward the depot base load 𝑥 𝑏𝑎𝑠𝑒 or the wholesale grid (determined via a set of binary constraints): Also, a cost of accelerated aging from increased battery cycling is included, 𝑝 𝑑𝑒𝑔 , $0.01/kWh injection (eq. 1b) 6 . The second part of (eq.…”
Section: Objective and Constraint Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The value of 𝑝 𝐸,𝑖𝑛𝑗 𝑡,𝑠 is a function of the relative share of injection going toward the depot base load 𝑥 𝑏𝑎𝑠𝑒 or the wholesale grid (determined via a set of binary constraints): Also, a cost of accelerated aging from increased battery cycling is included, 𝑝 𝑑𝑒𝑔 , $0.01/kWh injection (eq. 1b) 6 . The second part of (eq.…”
Section: Objective and Constraint Formulationmentioning
confidence: 99%
“…For instance, a study by Szinai et al reports that unmanaged EV charging will cost the California grid $120-$690 million of annual operating expenses in 2025 and require either generation capacity investment or costly imports to avoid blackout scenarios 5 . Further, a more recent study by Owens et al indicates that smart charging capabilities are particularly critical to economically achieving the low carbon pledges made by U.S. states 6 . Not to mention increasing electrification across buildings and industry and network bottlenecks, it is likely that a variety of integrated resources and demand side management strategies will be required to support increasing electric loads in decarbonizing power systems 7 .…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…One of them is installing 150 million tons of low-emission hydrogen by 2030, capturing about four Gt of emissions by 2035, and increasing the share of electric vehicles in new truck sales by half by 2035. A study by Owens 36 confirmed the importance of storage in the energy transition by modeling Vehicle to Energy (V2G) and found that the impact of V2G on system capacity and value in the New England Light Duty Vehicle fleet was 13.9% is significant, replacing stationary storage of around 14.7 GW. Furthermore, the blueprint believes that achieving NZE is based on global partnerships in various areas, such as innovation, including technology partnerships, to bring key technologies such as hydrogen, enhanced biofuels, carbon capture, use and storage (CCUS) to a commercial scale.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To satisfy the rapidly growing demand for lithium-ion batteries (LIBs) in the global market, the scientific community is focused on developing high-performance electrode materials. [1][2][3][4][5][6][7] Among several candidates, Li-excess oxides with a cation-disordered rocksalt (DRS) structure are promising positive electrode materials due to their high theoretical capacities (>350 mA h g -1 ). [8][9][10][11][12] DRS oxides used to be disregarded as a positive electrode material because of the absence of a lithium migration path in DRS structure.…”
Section: Introductionmentioning
confidence: 99%